Comparison of MRI T2 Relaxation Changes of Knee Articular Cartilage before and after Running between Young and Old Amateur Athletes - Cha, Jang Gyu; Lee, Jae Chul; Kim, Hyun Joo; Han, Jong Kyu; Lee, Eun Hye; Kim, Yong Dai; Jeon, Chan Hong (Korean journal of radiology, 2012)
To compare changes in T2 relaxation on magnetic resonance (MR) images of knee articular cartilage in younger and older amateur athletes before and after running. By using a 3.0-T MR imager, quantitative T2 maps of weight-bearing femoral and tibial articular cartilages in 10 younger and 10 older amateur athletes were acquired before, immediately after, and 2 hours after 30 minutes of running. Changes in global cartilage T2 signals of the medial and lateral condyles of the femur and tibia and regional cartilage T2 signals in the medial condyles of femoral and tibia in response to exercise were compared between the two age groups. Changes in global cartilage T2 values after running did not differ significantly between the age groups. In terms of the depth variation, relatively higher T2 values in the older group than in the younger group were observed mainly in the superficial layers of the femoral and tibial cartilage (p < 0.05). Age-related cartilage changes may occur mainly in the superficial layer of cartilage where collagen matrix degeneration is primarily initiated. However, no trend is observed regarding a global T2 changes between the younger and older age groups in response to exercise.